Study of EEG Findings in Patients Referred from Psychiatrists - Chowdhury, RN; Daisy, S; Rahman, KM; Khan, SU; Hasan, ATMH; Khan, ZR; Haque, B; Hoque, MA; Mondol, BA; Habib, M; et al. (Journal of Bangladesh College of Physicians and Surgeons, 2012)
EEG is not so commonly used in patients attending psychiatry department. It is predominantly required to rule out any organic cause behind the behavioral changes. Purpose of this study was to assess the referred cases from psychiatry department and determine the clinical factors associated with an abnormal EEG in patients with psychiatric problem. We retrospectively reviewed and analyzed the data of all the cases referred to EEG lab. of Dept. of Neurology, Dhaka Medical College Hospital from psychiatrist. A total of 50 patients from July 2009 to January 2011 were selected. From the EEG register following information were noted eg. age, sex, socioeconomic status, habitat, rural or urban, clinical features, associated features, probable clinical diagnosis and EEG findings. The results showed that most of the patients belonged to age group 11-20years, comprising 46 % (n-23), 66% (n-33) were female. Though the total rate of abnormal EEG in psychiatry patients are low (n-20). 44% of the patients having seizure as the presenting complaint had the largest number of EEG abnormality (n-16), p value <.001. Patients with primary psychiatric disorders did not have any epileptiform activity (n-22). Where as most of the patients (n- 27) who were undiagnosed at the time of referral had the largest number of EEG abnormality (n-19), p value<.002. So any patient presenting to psychiatry department with seizure disorder or any patient with diagnostic confusion should be evaluated with EEG. DOI: http://dx.doi.org/10.3329/jbcps.v30i1.11363 J Bangladesh Coll Phys Surg 2012; 30: 24-29